ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI - Komara, Acep; Ariningrum, Hardini (Universitas Malahayati, 2013)
This study is meant to test the effect of involvement variable, capability of personnelInformation System (IS), organization size, top management support and formalization to the systemuse and satisfaction of Accounting Information System (AIS) users as the surrogate of AISperformance. Besides, it is also meant to test the differences of AIS performance in relation to theusers education and training program, steering committee of IS and the independence of IS departmentlocation. This study is based on Sugiharto?s study (2001) with the change that lies on research focusi.e. at general ledger sub-system, research object, data processing analysis, and the instrument used tomeasure the satisfaction of AIS users. The research data are obtained by means of mail survey,enumerator service, and walk-in done by the researcher, directly to the respondents. There are 83manufacturing business involved in this research showing the level of 24.93 % response out of 333population. The analysis method of research comprises influence test using multiple regressionanalysis, t-test, F-test, coefficient of determination. Meanwhile, differential test uses Mann WhitneyU-test. The result of partial regression test shows that involvement variable, organization size, topmanagement support, and formalization have a significant effect to the users? satisfaction. Besides,involvement variable, capability, and top management support affect significantly to the use of AIS.Meanwhile, on the simultaneity test, all independent variables perceived to have an effect on the AISperformance. Furthermore,coefficient of determination for users? satisfaction variable (Y 1) and thesystem use (Y2) is 41.2% and 32.4% accordingly. On difference test using Mann Whitney U-test is tobe found evidence that there is no difference of AIS performance in line with whether or not there is asteering committee, user training andeducation program, and the independence or dependence of theIS department. The result of the researchheralds three implications for the hereinafter research. First,some variables of organizational context and moderating variables require to be entangled. Second, itneeds exploration and definition of techniquesand approaches for user training and education program.Third, it needs elaboration of special purpose of the software developed by the respondents.Keyword : User Accounting Information System Satisfaction, User Accounting Information Use,UserInvolvement, Capability of Information System Personnel, Top ManagementSupport, Formalization of Information System Development, Organization Size.